PERLINDUNGAN HUKUM NASABAH BANK PENGGUNA LAYANAN INTERNET BANKING DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Dinna Dayana La Ode Malim; Rachmat Taibu; Budi Setiawan (Jurnal Ilmu Hukum Kanturuna Wolio, 2022)
The formulation of the problem in this research are: 1. What is the form of legal protection for bank customers using internet banking services, 2. How to fulfill the rights and obligations of bank customers who are harmed by internet banking service users. The purpose of this research is to find out the legal protection for bank customers who are harmed due to errors in the bank system. This research is a type of normative legal research which is a systematic study of law. The type of data used is through literature study in the form of books, laws and regulations, documents and so on. Analysis of the data used is content analysis, then the data is presented descriptively.